2006
DOI: 10.1523/jneurosci.4071-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Directional Cuing of Target Choice in Human Smooth Pursuit Eye Movements

Abstract: Perceptual attention and target choice for movement have many features in common. In particular, both generally are based on selection of a particular location in space. To ask whether motor control, like attention, also can exhibit target choice based on nonspatial features of the stimulus, we assessed the initiation of smooth pursuit eye movements when two targets move in different directions after human subjects have been cued which direction or color to track. The direction cue consisted of a patch of dots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…Several behavioral results have shown that information about the direction of motion can be a strong cue for facilitating target selection for pursuit Garbutt and Lisberger 2006;Krauzlis and Adler 2001). Our results suggest that the directional selection for pursuit does not occur in the FPA.…”
Section: Implications For Target Selectionmentioning
confidence: 48%
“…Several behavioral results have shown that information about the direction of motion can be a strong cue for facilitating target selection for pursuit Garbutt and Lisberger 2006;Krauzlis and Adler 2001). Our results suggest that the directional selection for pursuit does not occur in the FPA.…”
Section: Implications For Target Selectionmentioning
confidence: 48%
“…In human subjects, eye movements were measured using a dual Purkinje image tracker. Details are available in Garbutt and Lisberger (2006). Procedures had been approved in advance by the Institutional Review Board at UCSF and informed consent was obtained.…”
Section: E T H O D Smentioning
confidence: 99%
“…When identical spot targets move in orthogonal directions across different parts of the visual field, the resulting initiation of pursuit can be modeled best as the vector average of the pursuit initiation evoked by the two stimuli singly . However, winner-take-all behavior emerges when a monkey or human is cued about which target to track (Ferrera and Lisberger 1995;Garbutt and Lisberger 2006;Recanzone and Wurtz 1999;Shichinohe et al 2009). Attempts to determine the site of the vector averaging for two spot targets have led to the conclusion that vector averaging is located downstream from the site(s) of motor learning in pursuit (Kahlon and Lisberger 1999) and the site(s) where the gain of visual-motor transmission is controlled (Tanaka and Lisberger 2002) by outputs from the smooth eye movement region of the frontal eye fields (Tanaka and Lisberger 2001).…”
mentioning
confidence: 99%